Information Technology Service Capabilities in Supporting Digital Government Transformation Toward Good Governance in Indonesia - Ningrum, Luci Fransiska Puspita (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
Digital transformation of government has become a strategic agenda in efforts to improve the quality of governance and public services in Indonesia. Although infrastructure development and information technology utilization show positive trends, the implementation of digital government still faces structural challenges, particularly limitations in digital human resource capacity, fragmentation of inter-agency systems, and increasing cybersecurity risks. This study aims to map information technology service capabilities and analyze their relevance as enablers of good governance in the context of Government Technology (GovTech) implementation in Indonesia. The study uses a qualitative approach with a literature review method of national policies, international agency reports, and relevant scientific publications. The results of the study show that the limitations of internal bureaucratic capacity make cooperation between the government and the private sector within the framework of Public Private Partnership (PPP) a crucial strategy. The development of the national information technology service ecosystem, particularly in managed services, cloud computing, system integration, and cybersecurity, provides structural support for strengthening digital government. Information technology service capabilities contribute significantly to improving administrative efficiency, system interoperability, data management transparency, and public service quality. This study confirms that information technology services are not merely supporting instruments, but rather strategic components in realizing adaptive, collaborative, and sustainable digital governance.